PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS PENDIDIKAN PROVINSI BALI: Studi Empiris pada Kantor Dinas Pendidikan Provinsi Bali - James Adolf Paparang; I Putu Bagus Suthanaya; I Gede Suastana (Universitas Triatma Mulya, 2021)
This study aims to determine between work motivation and work discipline on performance of civil servants at the Bali Provincial Education Office. This research is a quantitative study that describes and explains how the influence between work motivation and work discipline on performance on civil servants at the Bali Provincial Education Office. The population used was 108 employees and the sample used was 60% of the total population or as many as 65 respondents. Testing instruments using the validity and reliability test. Data analysis techniques used multiple linear regression, the classic assumption test, the coefficient of determination, and the t test. The results showed that (1) Work motivation has a positive effect on performance of Civil Servants at the Bali Provincial Education Office with a value of 0.275, (2) Work discipline has a positive effect on the performance of Civil Servants at the Provincial Education Office of Bali with a value of 0.642, (3) the magnitude of the influence of work motivation (X1) and work Discipline (X2) on the job satisfaction of Civil Servants at the Bali Provincial Education Office amounted to 92.5.8%. means the magnitude of the influence of work motivation (X1) and work discipline (X2) on performance (Y) is 92.5%, while the remaining 7.5% is determined by other variables outside of work motivation and work discipline which are not discussed in this study